Study on the Preparation and Performance of High-Pressure Sea Water Resistant Epoxy-Modified Polyurethane Urea Elastomer Coating Material - QI Xinyu, XIAO Mingming, TIAN Pan, WANG Yang, WU Zhengjiang (Cailiao Baohu, 2025)
In order to address the corrosion issues of metallic components in marine engineering,polyurethane urea elastomers were synthesized using polytetrahydrofuran ether diol (PTMG1000), diphenylmethane diisocyanate (MDI) and 4,4'-methylenebis(2-chloroaniline) (MOCA)as raw materials.The elastomers were modified with epoxy resin, and epoxy segments were introduced into the polyurethane molecular structure to prepare an amorphous structure of epoxy resin-modified polyurethane urea elastomer (PUU-s) as coating material.This modification was intended to enhance the mechanical properties, adhesion, water resistance and other properties of the coating material.A systematic investigation was conducted to evaluate the effects of epoxy resin E51 content on the mechanical properties, adhesion, water resistance, permeability resistance and corrosion resistance of the coating material in a synthetic seawater environment at 4.5 MPa and 25 ℃.The results showed that, with the increase in the amount of epoxy resin E51, the tensile strength, elongation at break and adhesion of the coating material first increased and then decreased, while the water absorption rate was gradually decreased.The permeability resistance and corrosion resistance were initially improved and subsequently were diminished.When the epoxy resin E51 content was maintained at 5%(mass fraction),the modified polyurethane urea was found to exhibit optimal overall performance.The tensile strength, elongation at break and adhesion of the modified polyurethane urea were measured to be 25.8 MPa, 605%and 14.5 MPa, respectively, representing improvements of 4.2 MPa, 45%and 5 MPa compared to the unmodified polyurethane urea.After soaking for 960 h, superior permeability resistance was demonstrated by the modified polyurethane urea；moreover, the substrate protected by the modified polyurethane urea was found to show no significant corrosion points compared to the unmodified polyurethane urea, indicating a certain degree of protective capability for the substrate.